Effect of growth temperature and ethanol flow rate on synthesis of single-walled carbon nanotube by alcohol catalytic chemical vapor deposition using Ir catalyst in hot-wall reactor. (18th December 2020) - Misaki, Ai; Saida, Takahiro; Naritsuka, Shigeya; Maruyama, Takahiro
Abstract: We carried out synthesis of single-walled carbon nanotubes (SWCNTs) in the hot-wall reactor by alcohol catalytic chemical vapor deposition using an Ir as a catalyst. By optimizing the ethanol flow rate, SWCNTs were grown at the growth temperature between 700 °C and 900 °C. Raman results using the four excitation wavelengths of 488, 532, 671 and 785 nm showed that the diameters of most SWCNTs grown from an Ir catalyst were less than 1.0 nm at 700 °C and 800 °C. When the growth temperature was above 800 °C, vertically-aligned SWCNTs were grown, and the thickness reached 1.8  μ m after the growth at 900 °C for 60 min under an ethanol flow rate of 500 sccm. However, at 900 °C, the diameters of SWCNTs were enlarged and most of them were distributed above 1 nm. Our result demonstrates that an Ir catalyst is useful to obtain small-diameter SWCNTs on a large scale.